The response of pre-osteoblasts and osteoclasts to gallium containing mesoporous bioactive glasses. (August 2018) - Gómez-Cerezo, N.; Verron, E.; Montouillout, V.; Fayon, F.; Lagadec, P.; Bouler, J.M.; Bujoli, B.; Arcos, D.; Vallet-Regí, M.
Graphical abstract: Abstract: Mesoporous bioactive glasses (MBGs) in the system SiO2 -CaO-P2 O5 -Ga2 O3 have been synthesized by the evaporation induced self-assembly method and subsequent impregnation with Ga cations. Two different compositions have been prepared and the local environment of Ga(III) has been characterized using 29 Si, 71 Ga and 31 P NMR analysis, demonstrating that Ga(III) is efficiently incorporated as both, network former (GaO4 units) and network modifier (GaO6 units). In vitro bioactivity tests evidenced that Ga-containing MBGs retain their capability for nucleation and growth of an apatite-like layer in contact with a simulated body fluid with ion concentrations nearly equal to those of human blood plasma. Finally, in vitro cell culture tests evidenced that Ga incorporation results in a selective effect on osteoblasts and osteoclasts. Indeed, the presence of this element enhances the early differentiation towards osteoblast phenotype while disturbing osteoclastogenesis. Considering these results, Ga-doped MBGs might be proposed as bone substitutes, especially in osteoporosis scenarios. Statement of Signifcance: Osteoporosis is the most prevalent bone disease affecting millions of patients every year. However, there is a lack of bone grafts specifically designed for the treatment of bone defects occurred because of osteoporotic fractures. The consequence is that osteoporotic bone defects are commonly treated with the same biomaterials intended for high quality bone tissue. In this work we have prepared mesoporous bioactive glasses doped with gallium, demonstrating osteoinductive capability by promoting the differentiation of pre-osteoblast toward osteoblasts and partial inhibition of osteoclastogenesis. Through a deep study of the local environment of gallium within the mesoporous matrix, this work shows that gallium release is not required to produce this effect on osteoblasts and osteoclasts. In this sense, the presence of this element at the surface of the mesoporous bioactive glasses would be enough to locally promote bone formation while reducing bone resorption.